1974
DOI: 10.3758/bf03198580
|View full text |Cite
|
Sign up to set email alerts
|

Auditory and linguistic processing of cues for place of articulation by infants

Abstract: infants~ere found to discriminate the acoustic cues for the phonetic feature of place of articulation III a categorical manner; that is, evidence for the discriminability of two synthetic sp~ech patter~s~as. pre~~nt only when the stimuli signaled a change in the phonetic feature of place. No evidence of discriminability was found when two stimuli, separated by the same acoustic difference, signaled acoustic variations of the same phonetic feature. Discrimination of the same acoustic cues in a nonspeech context… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
101
1
3

Year Published

1977
1977
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(111 citation statements)
references
References 24 publications
6
101
1
3
Order By: Relevance
“…Our results are consistent with those observed for speech stimuli (e.g., Eimas, 1974Eimas, , 1975aEimas et al, 1971), since infants displayed a reliable increase in sucking only for stimuli chosen from opposite sides of the adult categorical boundary.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Our results are consistent with those observed for speech stimuli (e.g., Eimas, 1974Eimas, , 1975aEimas et al, 1971), since infants displayed a reliable increase in sucking only for stimuli chosen from opposite sides of the adult categorical boundary.…”
Section: Discussionsupporting
confidence: 82%
“…Not only do infants make fine distinctions between speech sounds, but they do so in a categorical manner (i.e., they make interphonemic distinctions but not intraphonemic ones). Further, Eimas (1974Eimas ( , 1975b has shown that infants, like adults (Mattingly et aI., 1971), perceive certain acoustic cues categorically in speech contexts but not in nonspeech contexts. On the basis of these findings, Eimas (l975b and elsewhere) has suggested that the actual mechanisms which underlie the categorical perception of speech may be part of the biological makeup of the human infant.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Any infant who failed to meet the initial conditioning criterion (i.e., three in a row correct) on the Common pairing was excluded from the study as not being able (or interested) to perform the head-turn task, because much previous work has shown that infants of this age and younger (Eimas, 1974;Mehler, 1985) can discriminate /ba/ from /da/. On Days 2 and 3, infants were initially retested on Common to make sure they could (and would) still perform in the procedure.…”
Section: Methodsmentioning
confidence: 99%
“…The assumption that human listeners are innately sensitive to properties of the onset spectra for different places of stop consonant articulation could, as Stevens and Blumstein (e.g., 1978;Blumstein and Stevens, 1979) suggest, account for the ability of prelinguistic infants to discriminate place of articulation differences in synthetic three-formant and three-formant + burst stimuli (Eimas, 1974;Leavitt et al, 1976;Miller and Morse, 1976;Moffitt, 1971;Morse, 1972;Till, 1976;Williams and Bush, 1978). Although previous demonstrations of the infant's ability to discriminate place of articulation differences in stop consonants lend support to Stevens and Blumstein's argument, it is not known whether the onset spectra of the stimuli employed in these studies possessed the critical properties described by Stevens and Blumstein.…”
Section: Introductionmentioning
confidence: 99%